Promoting Critical Thinking through an SDG-Integrated STEAM E-Module for Grade X High School Students - Pauzi; Rayendra; Abna Hidayati; Ulfia Rahmi (Postgraduate, University of Mataram, 2026)
This research aims to produce STEAM-based E-Modules that are valid, practical, and effective in improving students' critical thinking skills in mathematics subjects. This research uses the ADDIE development model with five steps: Analysis, Design, Development, Implementation, and Evaluation. The validity of the E-Module was tested by four validators, namely experts in instruments, media, materials, and languages. Trial I involved 3 students, while trial II was carried out on 2 educators and 25 students. The results showed that the STEAM-based E-Module on linear program materials had excellent validity, with a score of 83% for product experts, 93% for subject matter experts, and 93% for linguists. The practicality of this E-Module is very high, with the trial of students obtaining a score of 98% and educators 96%, both of which are in the category of